Analysis of Tourism Village Products through Digital Marketing in Girimulyo Tourism Village - Pradipta, Made Prasta Yostitia (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
Rapid advancements in information technology have necessitated efficient use of data. This research evaluates the content on the Girimulyo Tourism Village website, [www.senatahadventure.com], in terms of completeness, speed, and efficiency through five dimensions of website facilities. By utilizing this technology, tourists can access comprehensive, timely, and efficient information. The data for this study were obtained by visiting the Senatah Adventure website and comparing it with other websites. This research employs five dimensions of information technology: information, communication, transactions, relationships, and technical excellence. The findings indicate that the website [www.senatahadventure.com] only meets the technical excellence dimension, which can be found via a Google search engine and has a fast-loading time. However, several deficiencies must be addressed to transform a website into a dynamic platform known to the broader community.